2016
DOI: 10.1111/1475-6765.12144
|View full text |Cite
|
Sign up to set email alerts
|

Pathways to power: Women's representation in the 2014 European Parliament elections

Abstract: The 2014 European Parliament (EP) elections produced a record proportion of women MEPs overall (37 per cent). Yet, these results vary widely across countries and parties. This article aims to explain these variations, evaluating not only who the elected representatives of the 8th EP are, but also how they got there. Are the paths to the EP the same for women and men? Are there gender differences in terms of MEPs’ political experience? A unique dataset listing more than 700 elected MEPs and their background, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 30 publications
2
25
0
Order By: Relevance
“…Directly, quotas can be a fast track for female candidates to get elected. Indirectly, intraparty quotas send a signal to women that their participation in politics is encouraged (Lühiste & Kenny 2016). 4 Third, we expect young parties to have a higher share of female representatives than older parties.…”
Section: Variables and Datamentioning
confidence: 98%
See 1 more Smart Citation
“…Directly, quotas can be a fast track for female candidates to get elected. Indirectly, intraparty quotas send a signal to women that their participation in politics is encouraged (Lühiste & Kenny 2016). 4 Third, we expect young parties to have a higher share of female representatives than older parties.…”
Section: Variables and Datamentioning
confidence: 98%
“…Directly, quotas can be a fast track for female candidates to get elected. Indirectly, intraparty quotas send a signal to women that their participation in politics is encouraged (Lühiste & Kenny )…”
Section: Variables and Datamentioning
confidence: 99%
“…For instance, Fortin‐Rittberger and Rittberger () study the candidate selection practices of 100 political parties across the EU and show that inclusiveness at an early stage is key to more gender balanced representation. Luhiste and Kenny, in turn, compiled a dataset of the backgrounds of more than 700 MEPs in the context of the 2014 EP elections and found that political parties were key determinants to women's electoral success with some pathways to power being very different for women than men (Lühiste and Kenny, ).…”
Section: Methodology and Research Materialsmentioning
confidence: 99%
“…The representation of women in the EP has risen steadily over the past decades, most recently from 35 per cent female MEPs in the 7 th legislature to 37 per cent in the 8 th legislature (see also Lühiste and Kenny, ; Kantola and Rolandsen Agustin, ). Big differences remain in the numbers of women elected by different member states.…”
Section: Background: the Gender Composition Of The Ep Party Groupsmentioning
confidence: 99%
“…In another study Pemstein et al (2015) identified incumbency as a factor that harm's women's nomination to party lists and their election to the EP. In addition, and focusing more on elections than nominations, Luhiste and Kenny (2016) reported that left-wing parties sent more women MEPs to Brussels and Strasbourg than center or right-wing parties. (2016) Right-leaning parties (reference category in the models) Dummy variable for right-wing and radical right-wing parties (1) for all parties with a value 6.01-10 on the ideological 0-10 scale in the ParlGov dataset Döring and Manow (2016)…”
Section: Case Selectionmentioning
confidence: 99%